2021
DOI: 10.3390/ijms22136993
|View full text |Cite
|
Sign up to set email alerts
|

CD74 and CD44 Expression on CTCs in Cancer Patients with Brain Metastasis

Abstract: Up to 40% of advance lung, melanoma and breast cancer patients suffer from brain metastases (BM) with increasing incidence. Here, we assessed whether circulating tumor cells (CTCs) in peripheral blood can serve as a disease surrogate, focusing on CD44 and CD74 expression as prognostic markers for BM. We show that a size-based microfluidic approach in combination with a semi-automated cell recognition system are well suited for CTC detection in BM patients and allow further characterization of tumor cells poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…Coexpression of CD44/MyD88 in advanced OC is associated with a decrease in progression-free and overall survival [ 35 ]. As reported by Loreth et al [ 36 ], CD44 is expressed on the majority of CTCs obtained from patients with breast cancer, non-small cell lung cancer and melanoma with brain metastases while being much less expressed in the metastatic tissue. The authors concluded that the appearance of CD44 on the CTC surface plays an important role in the trafficking of a viable cell through the circulatory bed.…”
Section: Discussionmentioning
confidence: 59%
“…Coexpression of CD44/MyD88 in advanced OC is associated with a decrease in progression-free and overall survival [ 35 ]. As reported by Loreth et al [ 36 ], CD44 is expressed on the majority of CTCs obtained from patients with breast cancer, non-small cell lung cancer and melanoma with brain metastases while being much less expressed in the metastatic tissue. The authors concluded that the appearance of CD44 on the CTC surface plays an important role in the trafficking of a viable cell through the circulatory bed.…”
Section: Discussionmentioning
confidence: 59%
“…The protein–protein interactome (PPI) network explored the network relationship between survival genes and used Cytoscape for visualization. Significantly high network nodes, IL10, CCL2, CD74, and HLA-DRA, were found to be responsible for tumorigenesis, macrophage enrichment, and immune response among others [ 36 38 ]. Thirty-eight prognostic genes were obtained by the COX analysis, and then, the top five genes with the most nodes were selected from the PPI network.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating tumor cells disseminated by primary or metastatic lesions have been identified in the peripheral blood of patients with IMD secondary to breast cancer, NSCLC, and melanoma [ 33 , 35 , 36 , 37 , 38 ]. Current research efforts have focused on the detection of CTCs as prognostic markers.…”
Section: Detection Of Genetic Alterations Associated With Imd Using Liquid Biopsymentioning
confidence: 99%
“…Genomic evidence suggests that there may be heterogeneity between CTCs due to specific metastatic organ sites, making the molecular characterization of CTCs one potential avenue to distinguish CTCs from distinct metastatic sites. Early evidence indicates that expression of CD44 and CD74 on CTCs, two proteins associated with the development of IMD, could be used to distinguish CTCs due to metastases to the brain from CTCs associated with other metastatic sites [ 37 , 38 ]. Considering the low overall detection rates of CTCs in patients with IMD using conventional assays, more in-depth investigations are required before CTCs can be reliably employed in a clinical setting for the prognosis and diagnosis of IMD.…”
Section: Detection Of Genetic Alterations Associated With Imd Using Liquid Biopsymentioning
confidence: 99%
See 1 more Smart Citation